Fatty acid composition of Nile tilapia (Oreochromis niloticus) and Red hybrid tilapia (Oreochromis mossambicus X Oreochromis niloticus) reared in intensive and extensive systems - Jamaudin, Siti Sarah; Omar, Mohamed Ariff; Goh, Yong Meng (2012)
Fish and marine mammals are among the richest sources of long–chain n-3 and n-6 polyunsaturated fatty acids (PUFA) in nature. As farmed fish becomes a major contributor to world fish supplies, hence it is important to maintain the high lipid nutritional quality of the product and to continue to provide large amounts of the health-promoting n-3 and n-6 PUFA to the consumers. Therefore, a study was conducted to examine the nutritional content, mainly fatty acid composition, of Nile (Oreochromis niloticus and Red hybrid tilapia (Oreochromis mossambicus x Oreochromis niloticus), derived from intensive and extensive culture systems. Twenty-two samples of Nile tilapia and 16 samples of Red tilapia cultured intensively and 10 samples of extensively cultured Nile tilapia were used in this study. All samples were subjected to total fatty acids extraction and their fatty acid compositions were determined using gas liquid chromatography. Results showed no significant differences in the concentration of saturated fatty acids (SFA) between intensively and extensively cultured Nile tilapia. For monounsaturated fatty acids (MUFA), the concentration was higher (p<0.05) in the intensively cultured Nile tilapia compared to the extensively cultured Nile tilapia. For n-3 PUFA, the concentration was higher (p<0.05) in Nile tilapia from the extensive system compared to Nile tilapia from the intensive system. But for n-6 PUFA, the intensively cultured Nile tilapia had a higher (p<0.05) concentration compared to the extensively cultured Nile tilapia. For n-6:n-3 PUFA ratio the intensively cultured Nile tilapia had a higher ratio (p<0.05) than the extensively cultured Nile tilapia. The different fatty acid composition of Nile tilapia cultured in different systems could be due to the different types of feed consumed by the fish. Future research could be directed at increasing the PUFA level in tilapia through the manipulation of the PUFA level in the fish diet.